MSD Competency Framework - Exchange, BEAM (2023)
MSD Competency Framework A catalogue of the full range of knowledge, s kills and aptitudes found in high-performing teams that use the market systems approach. Useful for: Practitioners - identify personal train ing needs and continue your professional development Trainers - divers ify your courses and refine your training / capacity-building offers M anagers - strengthen your recruitment and induction processes MSD comp etencies Competency is a mix of knowledge, skills and attitudes demons trated through concrete behaviours. This section explores the 17 compe tencies used by high-performing MSD teams. Arranged in three groups th ey relate to how we understand the world, make decisions and interact with others. Each competency is defined and has links to useful resour ces that explain or illustrate the knowledge or skills that feed it. W here available, sources of teaching and learning for that competency a re included. Teaching and learning modes An exploration of the most co mmon modes of teaching and learning that support practitioners to acqu ire knowledge, skills and attitudes. Some modes of learning are more r elevant to certain types of competency - as indicated by the box colou rs. Each page has a summary of the teaching mode, guidance for team le aders and trainers, and examples of how to use this mode for developin g specific competencies. Assessment modes Assessing competency is impo rtant for recruitment, performance appraisal and continued professiona l development These pages describe distinct approaches to evaluating i ndividuals. They include a summary of the evaluation mode, guidance fo r assessors, and examples tailored to specific competencies.